2018
DOI: 10.1111/acel.12794
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐31a‐5p from aging BMSCs links bone formation and resorption in the aged bone marrow microenvironment

Abstract: The alteration of age‐related molecules in the bone marrow microenvironment is one of the driving forces in osteoporosis. These molecules inhibit bone formation and promote bone resorption by regulating osteoblastic and osteoclastic activity, contributing to age‐related bone loss. Here, we observed that the level of microRNA‐31a‐5p (miR‐31a‐5p) was significantly increased in bone marrow stromal cells (BMSCs) from aged rats, and these BMSCs demonstrated increased adipogenesis and aging phenotypes as well as dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
143
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(153 citation statements)
references
References 62 publications
(75 reference statements)
4
143
0
Order By: Relevance
“…Western blot was performed using methods previously described in refs. 26 and 27. Briefly, cell lysates were separated on polyacrylamide–sodium dodecyl sulfate gel and electroblotted onto nitrocellulose membranes (Bio‐Rad, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Western blot was performed using methods previously described in refs. 26 and 27. Briefly, cell lysates were separated on polyacrylamide–sodium dodecyl sulfate gel and electroblotted onto nitrocellulose membranes (Bio‐Rad, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have revealed that stem cells could regulate the expression of specific genes in peripheral tissue cells by exosome-mediated transportation of miRNAs [40]. In this work, we screened a large number of differentially expressed miRNAs by comprehensive deep sequencing analysis of the small RNA profile from exosomes released by BMMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Age-related osteoporosis is a complex disease, and in order to study it, physiologically similar models are needed. It has been reported that SD rats more than 9 months old can be used for establishing an age-related bone loss model [27], and previous research has proven that male SD rats would develop osteoporosis naturally with age [28,29]. Therefore, aged SD rats were chosen as a model of senile bone loss in our research.…”
Section: Discussionmentioning
confidence: 99%